Powojenna metafora „bogostalina” w świetle „Żurnału Moskowskoj Patriarchii” = The Post-War Metaphor of Stalin-God as Presented in the Journal of the Moscow Patriarchate - Pawełczyk-Dura, Kamila (Studia religiologica, 2014)
Until the end of 1980s, the Journal of the Moscow Patriarchate was the only legitimate press organ of the Russian Orthodox Church. The publication of this journal was resumed after a break of near-ly eight years on 12 September 1943, the day of the enthronement of the Patriarch of Moscow and All Russia Sergius (Stragorodsky). Stalin’s consent to publish the religious journal showed the Church’s limited capacity to function in the political space of the Soviet state, assured to it at the end of World War II. Appreciating this gesture, the Orthodox clergy published several articles devo-ted to Stalin in the Journal. No other communist ever received such praise and interest from the Church either earlier or later.